Implementasi Model Pembelajaran Discovery Learning dalam Kemampuan Menulis Teks Ceramah di Kelas XI SMK Pelita Raya Kota Jambi - A, Febriyani Putri; D, Yusra; Rahmawati, Rahmawati (Universitas Batanghari Jambi, 2024)
This research aims to describe the implementation of the discovery learning model on the ability to write lecture texts in class XI at SMKS Pelita Raya, Jambi City. The approach used in this research is a qualitative approach with a descriptive research type. The data obtained in this research are the results of observations, interviews, and documentation regarding the implementation of the discovery learning model on the ability to write lecture texts in class XI Accounting 1 at SMKS Pelita Raya, Jambi City. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. Based on the results of implementing the discovery learning model on writing skills, teachers and students have implemented the discovery learning model. The teacher has implemented the discovery learning model in accordance with the steps of the discovery learning model, starting from the stages of designing lesson plans, implementing them, and evaluating them. Meanwhile, students become active and able to write a lecture text by paying attention to the structure and linguistic aspects.